2013
DOI: 10.1016/j.ijsu.2013.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral chronic subdural hematoma: What is the clinical significance?

Abstract: The frequency of focal neurological deficits was found to be lesser in patients with bilateral CSDH, and it may confound the diagnosis and delay treatment. To prevent neurological deterioration resulting from the thicker hematomas, early surgical decompression for bilateral CSDH should be implemented. Additionally, clinicians must be aware of the higher recurrent rate of bilateral CSDH after burr hole craniostomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
56
3
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 12 publications
3
56
3
2
Order By: Relevance
“…4,14 Bilateral cSDHs (bcSDHs) account for 17.4%-34.9% of cSDH cases. 7,17,19,21 Although there is no standardized treatment for cSDH and bcSDH, indication for surgery is generally accepted in symptomatic patients. Various surgical techniques have been used for years.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4,14 Bilateral cSDHs (bcSDHs) account for 17.4%-34.9% of cSDH cases. 7,17,19,21 Although there is no standardized treatment for cSDH and bcSDH, indication for surgery is generally accepted in symptomatic patients. Various surgical techniques have been used for years.…”
mentioning
confidence: 99%
“…1,2,[10][11][12]15 Moreover, in bcSDHs the retreatment rate reaches almost 30%. 7,13,19 Noted retreatment rates for bcSDHs in the literature depict both surgery for ipsilateral recurrence and surgery for contralateral progression after initial unilateral hematoma evacuation. Because of their different underlying pathomechanisms, ipsilateral recurrence and contralateral progression should be distinguished.…”
mentioning
confidence: 99%
“…Finally good recovery was observed in 28 patients according to GLASGOW OUTCOME SCALE and they left for home with satisfactory condition. (Table-III 20 conducted study in Taiwan and found traumatic brain injury in 73 (74.49%) of 98 patients. Rovlias et al 21 in Brazil found TBI in 503 (51.01%) out of 986 patients.…”
Section: Resultsmentioning
confidence: 99%
“…In literature, the unilateral chronic subdural hematoma is more frequent than the bilateral one [1,2]. The incidence of a bilateral CSDH is about 16-20% in population [3]. However, why some patients have unilateral and other bilateral hematoma or what determines the site of CSDH is not still quite clear.…”
Section: Introductionmentioning
confidence: 99%